Tick bite-induced alpha-gal syndrome and immunologic responses in an alpha-gal deficient murine model - Sharma, Surendra Raj; Choudhary, Shailesh K.; Vorobiov, Julia; Commins, Scott P.; Karim, Shahid (Frontiers in Immunology, 2024)
Alpha-Gal Syndrome (AGS) is a delayed allergic reaction due to specific IgE antibodies targeting galactose-α-1,3-galactose (α-gal), a carbohydrate found in red meat. This condition has gained significant attention globally due to its increasing prevalence, with more than 450,000 cases estimated just in the United States alone. Previous research has established a connection between AGS and tick bites, which sensitize individuals to α-gal antigens and elevate the levels of α-gal specific IgE. However, the precise mechanism by which tick bites influence the host's immune system and contribute to the development of AGS remains poorly understood. This study investigates various factors related to ticks and the host associated with the development of AGS following a tick bite, using mice with a targeted disruption of alpha-1,3-galactosyltransferase (AGKO) as a model organism. Methods Lone-star tick (Amblyomma americanum) and gulf-coast tick (Amblyomma maculatum) nymphs were used to sensitize AGKO mice, followed by pork meat challenge. Tick bite site biopsies from sensitized and non-sensitized mice were subjected to mRNA gene expression analysis to assess the host immune response. Antibody responses in sensitized mice were also determined.Our results showed a significant increase in the titer of total IgE, IgG1, and α-gal IgG1 antibodies titers in the lone-star tick-sensitized AGKO mice compared to the gulf-coast tick-sensitized mice. Pork challenge in Am. americanum -sensitized mice led to a decline in body temperature after the meat challenge. Gene expression analysis revealed that Am. americanum bites direct mouse immunity toward Th2 and facilitate host sensitization to the α-gal antigen., while Am. maculatum did not.This study supports the hypothesis that specific tick species may increase the risk of developing α-gal-specific IgE and hypersensitivity reactions or AGS, thereby providing opportunities for future research on the mechanistic role of tick and host-related factors in AGS development.